Neoantigen-reactive T cells exhibit effective anti-tumor activity against colorectal cancer. Issue 1 (31st December 2022) - Yu, Yaojun; Zhang, Jing; Ni, Leyi; Zhu, Yuesheng; Yu, Hejie; Teng, Yangyang; Lin, Limiao; Xue, Zhanxiong; Xue, Xiangyang; Shen, Xian; Song, Haiping; Su, Xiaoping; et al.
ABSTRACT: Neoantigens play a crucial role in cancer immunotherapy. However, the effectiveness and safety of neoantigen-based immunotherapies in patients with colorectal cancer (CRC), particularly in the Chinese population, have not been well studied. This study explored the feasibility and effectiveness of neoantigens in the treatment of CRC. Whole-exome sequencing (WES) and transcriptome sequencing were used to identify somatic mutations, RNA expression, and human leukocyte antigen (HLA) alleles. Neoantigen candidates were predicted, and immunogenicity was assessed. The neoantigens TSHZ3-L523P, RARA-R83H, TP53-R248W, EYA2-V333I, and NRAS-G12D from Patient 4 (PW4); TASP1-P161L, RAP1GAP-S215R, MOSPD1-V63I, and NAV2-D1973N from Patient 10 (PW10); and HAVCR2-F39V, SEC11A-R11L, SMPDL3B-T452M, LRFN3-R118Q, and ULK1-S248L from Patient 11 (HLA-A0201 + PW11) induced a heightened neoantigen-reactive T cell (NRT) response as compared with the controls in peripheral blood lymphocytes (PBLs) isolated from patients with CRC. In addition, we identified neoantigen-containing peptides SEC11A-R11L and ULK1-S248L from HLA-A0201 + PW11, which more effectively elicited specific CTL responses than the corresponding native peptides in PBLs isolated from HLA-A0201 + PW11 as well as in HLA-A2.1/K b transgenic mice. Importantly, adoptive transfer of NRTs induced by vaccination with two mutant peptides could effectively inhibit tumor growth in tumor-bearing mouse models. These data indicate that neoantigen-containing peptides with high immunogenicity represent promising candidates for peptide-mediated personalized therapy. Abbreviations: CRC: colorectal cancer; DCs: dendritic cells; ELISPOT: enzyme-linked immunosorbent spot; E:T: effector:target; HLA: human leukocyte antigen; MHC: major histocompatibility complex; Mut: mutant type; NGS: next-generation sequencing; NRTs: neoantigen-reactive T cells; PBMCs: peripheral blood mononuclear cells; STR: short tandem repeat; PBLs: peripheral blood lymphocytes; PBS: phosphate-buffered saline; PD-1: programmed cell death protein 1; TILs: tumor-infiltrating lymphocytes; RNA-seq: RNA sequencing; Tg: transgenic; TMGs: tandem minigenes; WES: whole-exome sequencing; WT: wild-type.